2023
DOI: 10.3390/chemosensors11120579
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy, a Tool for the Non-Destructive Sensory Analysis of Plant-Based Foods and Beverages: A Comprehensive Review

Teodora Basile,
Domenica Mallardi,
Maria Francesca Cardone

Abstract: In recent years, there has been a significant rise in the popularity of plant-based products due to various reasons, such as ethical concerns, environmental sustainability, and health benefits. Sensory analysis is a powerful tool for evaluating the human appreciation of food and drink products. To link the sensory evaluation to the chemical and textural compositions, further quantitative analyses are required. Unfortunately, due to the destructive nature of sensory analysis techniques, quantitative evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 150 publications
(218 reference statements)
0
1
0
Order By: Relevance
“…The near infrared hyperspectral imaging is applicable to solid samples as well as liquid samples, thus the variety of its applications in food technologies to a large range of food products. Several studies using the near infrared hyperspectral technology have contributed to various areas of food technologies including food quality control and authentication (18,19,20,21), food safety assessment (22,23,24,25), food process monitoring and optimization (26,27,28), food shelf-life prediction (29,30), food ingredients analysis (31,32), food allergens detection (33,34), and food sorting and grading (35). These research works showed that NIR-HSI covers notable areas of food technologies.…”
Section: Near Infrared Hyperspectral Imaging In Food Technologiesmentioning
confidence: 99%
“…The near infrared hyperspectral imaging is applicable to solid samples as well as liquid samples, thus the variety of its applications in food technologies to a large range of food products. Several studies using the near infrared hyperspectral technology have contributed to various areas of food technologies including food quality control and authentication (18,19,20,21), food safety assessment (22,23,24,25), food process monitoring and optimization (26,27,28), food shelf-life prediction (29,30), food ingredients analysis (31,32), food allergens detection (33,34), and food sorting and grading (35). These research works showed that NIR-HSI covers notable areas of food technologies.…”
Section: Near Infrared Hyperspectral Imaging In Food Technologiesmentioning
confidence: 99%
“…Fast, non-destructive near-infrared spectroscopy is already widely used in the agrifood and agricultural sectors, offering the advantage of promoting sustainable agriculture by eliminating the need for chemical reagents, minimizing environmental impact, and ensuring resource-efficient farming practices [14]. It is a vibrational spectroscopy that studies the interaction between electromagnetic radiation and chemical bonds in matter [15].…”
Section: Introductionmentioning
confidence: 99%